Delayed Chain Termination Protects the Anti-hepatitis B Virus Drug Entecavir from Excision by HIV-1 Reverse Transcriptase - Tchesnokov, Egor P. (American Society for Biochemistry and Molecular Biology, 2008)
Entecavir (ETV) is a potent antiviral nucleoside analogue that is used to treat hepatitis B virus (HBV) infection. Recent clinical studies have demonstrated that ETV is also active against the human immunodeficiency virus type 1 (HIV-1). Unlike all approved nucleoside analogue reverse transcriptase RT) inhibitors (NRTIs), ETV contains a 3′-hydroxyl group that allows further nucleotide incorporation events to occur. Thus, the mechanism of inhibition probably differs from classic chain termination. Here, we show that the incorporated ETV-monophosphate (MP) can interfere with three distinct stages of DNA synthesis. First, incorporation of the next nucleotide at position n + 1 following ETV-MP is compromised, although DNA synthesis eventually continues. Second, strong pausing at position n + 3 suggests a long range effect, referred to as “delayed chain-termination.” Third, the incorporated ETV-MP can also act as a “base pair confounder” during synthesis of the second DNA strand, when the RT enzyme needs to pass the inhibitor in the template. Enzyme kinetics revealed that delayed chain termination is the dominant mechanism of action. High resolution foot-printing experiments suggest that the incorporated ETV-MP “repels” the 3′-end of the primer from the active site of HIV-1 RT, which, in turn, diminishes incorporation of the natural nucleotide substrate at position n + 4. Most importantly, delayed chain termination protects ETV-MP from phosphorolytic excision, which represents a major resistance mechanism for approved NRTIs. Collectively, these findings provide a rationale and important tools for the development of novel, more potent delayed chain terminators as anti-HIV agents.